Trabecular bone texture detected by plain radiography is associated with an increased risk of knee replacement in patients with osteoarthritis: a six year prospective follow up study - Podsiadlo, Pawel; Ciccuttini, F; Wolski, Marcin; Stachowiak, Gwidon; Wluka, A (Elsevier Ltd, 2013)
Objective: To examine the association between trabecular bone texture and knee joint replacement (KJR) measured using a variance orientation transform (VOT) method. Methods: The association of trabecular bone texture and KJR was examined prospectively over 6 years in 123 subjects with symptomatic knee osteoarthritis (OA): data regarding KJR was available for 114 (93%). At baseline, weight-bearing anteroposterior tibio-femoral radiographs were acquired. Trabecular bone texture regions were selected from the medial and lateral subchondral tibia. The VOT method was applied to each region and five fractal bone texture parameters, i.e., mean fractal dimension (FDMEAN), fractal dimensions in the horizontal (FDH) and vertical (FDV) directions, and along the roughest part of trabecular bone (FDSta), and texture aspect ratio (Str) were calculated. The association between groups with increasing baseline fractal parameters (defined using tertiles) with risk of JR was examined using logistic regression. Results: 28 (25%) participants' study knees underwent KJR over 6 years. Participants with KJR had lower medial FDMEAN and FDH parameters (P=0.02 for difference). With increasing FDMEAN, adjusted for age, gender, body mass index (BMI), osteophyte grade, joint space narrowing (JSN) grade and WOMAC pain score, the odds of KJR was reduced (P=0.04 for trend). Conclusion: This study suggests that the texture of medial tibial trabecular bone measured from plain radiographs is related to the risk of KJR: with increasing FDMEAN (the overall measure of bone texture roughness) the risk of KJR was reduced, independent of other clinical predictors of joint replacement. Tibial trabecular bone texture may be a useful marker of disease progression and a target of therapy in OA.